2001
DOI: 10.1111/j.1574-6941.2001.tb00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the succession of bacterial communities in the Great South Bay (Long Island)

Abstract: Bacterial community composition and succession were examined over the course of the summer season in the Great South Bay, Long Island, NY, USA, using a 16S rDNA clone library approach. There was a progression of changes in dominant species in the libraries during the summer of 1997. The July library had several groups dominant, the SAR407 relatives of the alpha-Proteobacteria (24%) and the SAR86 (18%), sulfur-oxidizing symbiont relatives (8%) of the gamma-Proteobacteria, and unidentified Cytophaga-Flexibacter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
2
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 38 publications
4
36
2
2
Order By: Relevance
“…In 16S rDNA studies, this group is rarely found in pelagic samples, having been reported only during enrichments, e.g. during a brown tide bloom of Aureococcus anophagefferens (Kelly & Chistoserdov 2001) and in a mesocosm diatom bloom (Riemann et al 2000). However, we did not determine if this phylotype would have been missed in a multi-liter sample.…”
contrasting
confidence: 39%
“…In 16S rDNA studies, this group is rarely found in pelagic samples, having been reported only during enrichments, e.g. during a brown tide bloom of Aureococcus anophagefferens (Kelly & Chistoserdov 2001) and in a mesocosm diatom bloom (Riemann et al 2000). However, we did not determine if this phylotype would have been missed in a multi-liter sample.…”
contrasting
confidence: 39%
“…1 (see SI Tables 3-7 for details) or in the complex medium SYPG containing the following compounds per liter of distilled water: 35.0 g of sea salts, 0.5 g of yeast extract, 0.25 g of Trypticase peptone, and 0.1 g of sodium L-glutamate. Utilization of substrates was tested in a mineral medium containing (per liter) 35.0 g of sea salts, 0.1 g of NH 4 Cl, 0.05 g of K 2 HPO 4 , and 10 ml of a vitamin solution (see DSMZ medium 141, www.dsmz.de). Standard tests for the detection of enzymes like catalase, oxidase, lipase/esterase, and proteases were done according to the protocols given in ref.…”
Section: Methodsmentioning
confidence: 99%
“…In the following years, many sequences have been retrieved that were related to the clone OM60 (e.g., refs. [3][4][5][6][7][8]. By the end of 2005, Ͼ180 partial and full length 16S rRNA sequences available within the public databases were related to KT71 and OM60.…”
Section: N 1999 Eilers Et Al (1) Isolated a Bacterial Strain Desimentioning
confidence: 99%
“…Natural clean water of station IV was fetched every two or three days during the experiment for nearly 40 days. During this time, the species of station IV also had a seasonal succession, because it has reported that community composition can change drastically within weeks (Kelly and Chistoserdov, 2001). This is why the average similarity coefficient of within-sample was just 0.33 but not higher.…”
Section: Discussionmentioning
confidence: 92%
“…Many works have been reported to study the structural and functional variables of aquatic communities in relation to the ecological succession (Kowalchuk et al, 2000;Kelly and Chistoserdov, 2001;Merila et al, 2002;Noll et al, 2005;Michail et al, 2005). Since the last decade of last century, nature management has embodied a lot of projects to restore damaged ecosystems (Hemerik and Brussaard, 2002;Clewell and Aronson, 2006).…”
Section: Introductionmentioning
confidence: 99%